Implications of the scientific worldview on Muslim youths: an analytic approach - Hasan, Md Maruf; Ali, Mohd Mumtaz (IIUM Press, 2025)
There is a trend of Islamophobia within Muslim societies nowadays. The scientific worldview can be one of the root causes of Islamophobia. Muslim youths may develop nihilistic tendencies about our universe due to the influence of the scientific worldview. It is noticeable that New Atheism in the 21st century is one of the variants of the scientific worldview promoting the notion that Allah/God as no trace in the creation of the universe. Hence, all religious scriptures should be negated as the ultimate source of truth, and these scriptures should be treated as literary masterpieces in world literature at most. Popular science books as well as Hollywood culture may influence Muslim youths to subscribe subconsciously and consciously to the scientific worldview instead of the Islamic worldview. This research uses qualitative methodology. Library resources and internet resources would be utilized to comprehend the influence of the scientific worldview among Muslim youths. This research suggests that some early and contemporary Muslim scholars reacted to the scientific worldview and these responses can help to formulate new responses against New Atheism. This research would help to understand the inherent link between scientific worldview and Islamophobia among Muslim Youths.